Evolution induced state shifts in a long-term microbial community experiment - Mikko Kivikoski; Johannes Cairns; Shane L. Hogle; Sanna Pausio; Lutz Becks; Ville Mustonen; Teppo Hiltunen (Proceedings of the National Academy of Sciences, 2026)
Biological communities are complex, dynamic systems that underpin ecosystem functionality, yet their long-term dynamics and predictability remain poorly understood. Understanding how Darwinian evolution shapes these systems through eco-evolutionary feedback is a central challenge in ecology and evolution. Experimental studies using simplified microbial assemblages have yielded important insights into the ecological principles governing community states. However, an important knowledge gap is how selection within member species drives changes of community state in multispecies systems. Here, we present a four-year evolution experiment involving a 23-species synthetic bacterial community propagated in two environments: a control medium and the same medium supplemented with the antibiotic streptomycin. Through combined analyses of community composition and genome evolution, we quantified the temporal changes in species abundances and the evolutionary trajectories of individual community members. The extended duration of the experiment enabled the detection of adaptive mutations and community state shifts that occur only over long evolutionary timescales. We show that community dynamics are environment dependent and reproducible across replicates and that evolution of streptomycin resistance in a previously streptomycin-sensitive species on its own can induce abrupt community state shifts. Our results provide a direct demonstration of eco-evolutionary feedbacks within a multispecies community, revealing how a single adaptive mutation can reorganize complex ecological networks.